Hierarchically-structured large superelastic deformation in ferroelastic-ferroelectrics. (December 2019) - Deng, Yu; Gammer, Christoph; Ciston, Jim; Ercius, Peter; Ophus, Colin; Bustillo, Karen; Song, Chengyu; Zhang, Ruopeng; Wu, Di; Du, Youwei; Chen, Zhiqiang; Dong, Hongliang; et al.
Abstract: Large superelastic deformation in ferroelastic-ferroelectrics (FMs) is a complex phenomenon involving multiple mechanisms operating simultaneously. Understanding how these mechanisms contribute corporately is critical to apply this useful property to the intrinsically brittle FMs, which can therefore display both excellent functional and mechanical performance. Here, we have directly observed and quantitatively analyzed in situ in a transmission electron microscope the three main mechanisms of twinning domain, phase transformation and mobile point defect contributing to extremely large superelastic deformation in single-crystal BaTiO3 (5.0% strain) and Pb(Mg1/3 Nb2/3 )O3 -PbTiO3 (10.1% strain). Our results reveal the hierarchical origin of large recoverable strain in "brittle" FMs. Graphical abstract: Image, graphical abstract